2018
DOI: 10.5055/jom.2010.0004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous opioid patient-controlled analgesia with and without background infusion on respiratory depression: A meta-analysis

Abstract: Background: Although the addition of a background infusion for intravenous patient-controlled analgesia (IV-PCA) has been identified as a risk factor for the development of respiratory depression, this has not clearly been examined in a systematic fashion. The authors undertook a systematic review and meta-analysis of available randomized controlled trials (RCTs) to examine whether the addition of a background or continuous infusion to an IV-PCA regimen would be associated with an increased risk of respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 0 publications
1
31
1
Order By: Relevance
“…This initial subject cohort documented the feasibility of the study protocol and the PCA dosing guidelines, but demonstrated the continued challenges of recruiting SCD subjects to an in-patient interventional clinical trial. As seen in previous opioid PCA studies, the use of substantial PCA demand doses with modest continuous infusions (HDLI) in adult subjects in this study resulted in larger total cumulative opioid utilizations than a strategy relying predominantly on continuous higher opioid infusions with small demand doses (LDHI) [8]. However, similar paradigms in children showed little difference reflecting a smaller use of available demand doses [13].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…This initial subject cohort documented the feasibility of the study protocol and the PCA dosing guidelines, but demonstrated the continued challenges of recruiting SCD subjects to an in-patient interventional clinical trial. As seen in previous opioid PCA studies, the use of substantial PCA demand doses with modest continuous infusions (HDLI) in adult subjects in this study resulted in larger total cumulative opioid utilizations than a strategy relying predominantly on continuous higher opioid infusions with small demand doses (LDHI) [8]. However, similar paradigms in children showed little difference reflecting a smaller use of available demand doses [13].…”
mentioning
confidence: 65%
“…Current PCA strategies for severe pain typically include an opioid given by continuous infusion in addition to the PCA demand doses, but the addition of continuous opioid infusions has often been associated with increased opioid-related adverse effects [8],[9],[10]. To provide an evidence base for the clinical use of opioid PCA for sickle cell acute pain management, it is crucial to compare different PCA dosing approaches to determine their safety and efficacy.…”
mentioning
confidence: 99%
“…This lower level yet very valuable evidence has only recently been confirmed in a meta-analysis which found a higher incidence of respiratory events with the routine use of background infusions in adult but not pediatric patients [40 ].…”
Section: Quality Of Evidencementioning
confidence: 93%
“…If a patient cannot tolerate oral medications, PCA can provide continuous infusion of medication to provide basal analgesia, though the risk of oversedation and respiratory depression is increased. 28 For our clinical example, we recommend increasing the preadmission TDD of opioids (180 mg morphine equivalents) by 25% (225 mg) and administering as morphine 75 mg sustained-release every 8 hours to provide baseline analgesia and prevent withdrawal symptoms. The acute pain can be managed by initiating morphine PCA without continu- ous infusion at 0.5 mg bolus every 8 minutes as needed for breakthrough pain or oral morphine 30 mg immediate-release tablets every 3 hours as needed for pain.…”
Section: Acute Pain Management Clinical Example: Heroin Usermentioning
confidence: 99%